2022
DOI: 10.1039/d1ra08989g
|View full text |Cite
|
Sign up to set email alerts
|

Terbium doped LiLuF4 nanocrystal scintillator-based flexible composite film for high resolution X-ray imaging

Abstract: The flexible scintillation film has high X-ray imaging spatial resolution, in which LiLuF4:15% Tb scintillation nanocrystals have excellent radioluminescence properties and low detection limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The life-times of 4f-4f transitions in most trivalent lanthanide ions vary from a few µs to tens of ms [213,214], which are not suitable for real-time dynamic XEOL imaging. Although the decay rate of Ce 3+ ions is in the nanosecond range, XEOL emission in fluoride NSs doped by cerium ions is in the UV region [188,189], which do not match well with commonly used visible detectors. So to achieve bright XEOL intensity with fast decay rate and appropriate emission wavelength range, it is better to design the local crystal environment of 5d orbitals of Ce 3+ and Eu 2+ ions in fluoride NSs for the realization of better XEOL performances.…”
Section: Existing Challenges and Future Opportunitiesmentioning
confidence: 78%
See 1 more Smart Citation
“…The life-times of 4f-4f transitions in most trivalent lanthanide ions vary from a few µs to tens of ms [213,214], which are not suitable for real-time dynamic XEOL imaging. Although the decay rate of Ce 3+ ions is in the nanosecond range, XEOL emission in fluoride NSs doped by cerium ions is in the UV region [188,189], which do not match well with commonly used visible detectors. So to achieve bright XEOL intensity with fast decay rate and appropriate emission wavelength range, it is better to design the local crystal environment of 5d orbitals of Ce 3+ and Eu 2+ ions in fluoride NSs for the realization of better XEOL performances.…”
Section: Existing Challenges and Future Opportunitiesmentioning
confidence: 78%
“…It was reported that the LiLuF 4 possessed a higher absorption coefficient than those of CdTe, BaF 2 , CdZnTe, and CsPbBr 3 materials at a higher photon energy, and the detection limit of LiLuF 4 :15 Tb NSs was measured to be 36.31 nGy s −1 , which is much lower than typically used for X-ray diagnostics (5.50 µGy s −1 ). The LiLuF 4 :15 Tb NSs involved film was verified to be used for XEOL imaging to reveal the details of circuit board with a spatial resolution better than 20 lp mm −1 [188]. For dynamic real-time X-ray imaging, it remains a great challenge to develop divalent lanthanide or metal transition activators doped fluoride NSs with fast decay time.…”
Section: Xeol Imagingmentioning
confidence: 99%
“…An essential feature of LiLuF 4 is its uniaxial crystal nature, possessing a scheelite crystal structure with space group I 41/ a . In this structure, Lu 3+ ions are coordinated by eight F – ions and occupy a crystal site with local S4 symmetry (Figure a) . By comparison of the standard cards of LiLuF 4 and NaLuF 4 , noticeable differences can be observed.…”
Section: Resultsmentioning
confidence: 97%
“…In this structure, Lu 3+ ions are coordinated by eight F − ions and occupy a crystal site with local S4 symmetry (Figure 3a). 30 By comparison of the standard cards of LiLuF 4 and NaLuF 4 , noticeable differences can be observed. LiLuF 4 belongs to the tetragonal system (with an a:b:c ratio of 5.13:5.13:10.54), while NaLuF 4 belongs to the hexagonal system (with an a:b:c ratio of 5.90:5.90:3.45; Figure 3c).…”
Section: Nir Luminescence Imaging and Ct Imagingmentioning
confidence: 99%
“…However, the quenching phenomenon observed with the XEL spectra is dissimilar to the PL spectra (Figure S9b). This inconsistency could be due to the excitation specimen with two different excitation sources: UV light and X-rays, different nonradiative recombination processes within the host material, or the involvement of different energy transfer mechanisms, which include thermal quenching, saturation of active sites, defects and traps, radiation defects, and reabsorption of emitted light. Figure c illustrates the scintillation mechanism in Cs 2 NaGdCl 6 :Tb 3+ crystals, encompassing three processes: conversion, transportation, and luminescence. , At the conversion stage, X-rays interact with the heavy atoms in the host matrix, generating numerous hot electrons and deep holes, i.e., highly energetic charge carriers, through the photoelectric effect or Compton scattering. An avalanche of secondary electron–hole pairs is produced via electron–electron scattering and the Auger process, generating low-kinetic energy charge carriers.…”
Section: Resultsmentioning
confidence: 99%